Pemberdayaan Gen-Z Melalui Ide Pembuatan Gelas Motivasi (Mug Booster) - Nurhayati Nurhayati; Jessika Amanda Tasik; Dela Mahrita; Asniawati Asniawati; Bintang Pranata (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Mug Booster is a type of small-scale craft that specifically only produces various kinds of Mugs bearing motivational words. The Booster Mug is made of paper cups & glass cups whose exterior appearance is designed with motivational words. This Mug Booster can be an encouragement. This Mug Booster can also be used as a souvenir, gift or for personal use for people who read the motivational words that have been written. The purpose of this activity is to increase knowledge and skills. The approach used is community development through training and assistance to productive economic partners, namely the Z generation group in East Banjarmasin District. The results of the dedication show an increase in knowledge, skills in product management.